Drivers of decoupling economic growth from carbon emission: Empirical analysis of ASEAN countries using decoupling and decomposition model - Sher Khan; Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The exponential rise in energy-related carbon emissions poses a severe risk to both human and other species on the earth. The existence of a two-way relationship between economic growth and energy-specific carbon emissions needs to be delinked to achieve a low carbon economy. The current study analyzes the decoupling relationship between economic growth and carbon emissions for the Association of Southeast Asian Nations (ASEAN) countries as a region and at the national level. Moreover, Tapio decoupling indicator accompanied with decomposition techniques are employed to analyze the decoupling status and the drivers of carbon emissions. The findings state that the overall ASEAN region experienced expensive negative decoupling (END) status, followed by weak decoupling (WD) status, however at a national level, Singapore experienced the most significant strong decoupling (SD) status, while other countries mostly experienced END and WD status. The Log Mean Divisia Index (LMDI) decomposition results suggest that population, affluence, and energy structure significantly contributed to the carbon emissions at both regional and national levels. Besides, energy intensity and carbon intensity help to reduce carbon emissions in most of the ASEAN countries. Moreover, the extended decomposition model results state that population, affluence, and energy structure are the major forces that restrict the decoupling process, while energy intensity and carbon intensity help to strengthen the decoupling outcome, thereby driving the ASEAN countries towards the emission-free region. The current study contributes in highlighting key drivers of carbon emissions and gives extensive insights for emission mitigation. In turn, it also helps to foster sustainable economic growth.
Keywords: 330; ASEAN countries; carbon intensity; CO2 emissions; energy intensity; energy structure; Log Mean Divisia index; Tapio decoupling index